Cortical and frontal atrophy are associated with cognitive impairment in age-related confluent white-matter lesion. Issue 1 (8th September 2010) - Mok, Vincent; Wong, Kelvin K; Xiong, Yunyun; Wong, Adrian; Schmidt, Reinhold; Chu, Winnie; Hu, Xintao; Lung Leung, Eric Yim; Chen, Sirong; Chen, Yangkun; Tang, W K; Chen, Xiangyan; et al.
Abstract : Objective: Although age-related confluent white-matter lesion (WML) is an important substrate for cognitive impairment, the mechanisms whereby WML induces cognitive impairment are uncertain. The authors investigated cognitive predictors in patients with confluent WML. Methods: Among 100 patients with ischaemic stroke with confluent WML on MRI, the authors assessed executive function and global cognition by the Mattis Dementia Rating Scale—Initiation/Perseveration Subscale (MDRS I/P) and Mini-Mental State Examination (MMSE), respectively. All volumetric measures were corrected for intracranial volume. The authors investigated the association between basic demography, vascular risk factors, APOE status, WML volume, infarct measures (volume, number, location), microbleed number, atrophy measures (global, central, regional) and cognitive performance. The authors also performed Pittsburgh Compound B (PIB) imaging among seven cognitive impaired patients with stroke. Results: WML was no longer related to cognitive performance after adding atrophy into regression equations. Multivariate regression models showed that cortical grey matter volume independently accounted for performance on both the MDRS I/P (β=0.241, p=0.045) and MMSE (β=0.243, p=0.032). Models examining frontal subregions revealed that volumes of both left (β=0.424, p<0.001) and right (β=0.219, p=0.045) lateral frontal orbital gyri predicted MDRS I/P, whereas education (β=0.385, p<0.001) and left lateral frontal orbital gyrus (β=0.222, p=0.037) predicted MMSE. Volumes of WML and cognitively relevant brain regions were significantly associated. Seven patients with PIB imaging showed no uptake pattern typical of Alzheimer's disease, suggesting a predominantly vascular aetiology for the cognitive impairment and brain changes in these patients. Conclusions: Cognitive impairment in patients with confluent WML is mediated by global and frontal cortical atrophy.